Lithium secondary battery cathode active material, method for manufacturing the same and lithium secondary battery
Patent Information
- Application Number
- JP2024143314
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-28
- Filing Date
- 2024-08-23
- Publication Date
- 2025-03-12
Smart Images

Figure 2025032997000006 
Figure 2025032997000007 
Figure 2025032997000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, a method for producing the same, and a lithium secondary battery. [Background technology]
[0002] Conventionally, lithium cobalt oxide has been used as a positive electrode active material for lithium secondary batteries. However, since cobalt is a rare metal, lithium nickel manganese cobalt composite oxides with a low cobalt content have been developed (for example, see Patent Documents 1 and 2).
[0003] It is known that lithium secondary batteries that use a lithium nickel manganese cobalt composite oxide as a positive electrode active material can reduce costs by adjusting the atomic ratio of nickel, manganese, and cobalt contained in the composite oxide, and also have a higher capacity than lithium cobalt oxide (see, for example, Patent Document 3).
[0004] However, even with these conventional techniques, the lithium secondary battery using the lithium nickel manganese cobalt composite oxide as the positive electrode active material still has the problem of deterioration of cycle characteristics.
[0005] As a method for improving the cycle characteristics of a lithium secondary battery using a lithium nickel manganese cobalt composite oxide as a positive electrode active material, a method of coating the particle surface of the lithium nickel manganese cobalt composite oxide with a Ti-containing compound has been proposed (see, for example, Patent Document 4 and Patent Document 5). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2004 / 092073 Brochure [Patent Document 2] JP 2005-25975 A [Patent Document 3] JP 2011-23120 A [Patent Document 4] JP 2016-24968 A [Patent Document 5] JP 2016-72071 A Summary of the Invention [Problem to be solved by the invention]
[0007] In recent years, lithium secondary batteries have been considered for use in the field of automobiles, such as electric vehicles, hybrid vehicles, and plug-in hybrid vehicles. For this reason, there is a demand for further improvement in the cycle characteristics of lithium secondary batteries that use lithium nickel manganese cobalt composite oxide as the positive electrode active material.
[0008] Therefore, an object of the present invention is to provide a positive electrode active material for lithium secondary batteries that can impart excellent cycle characteristics to lithium secondary batteries that use a lithium nickel manganese cobalt composite oxide as a positive electrode active material, an industrially advantageous method for producing the same, and a lithium secondary battery that has excellent cycle characteristics. [Means for solving the problem]
[0009] The present inventors have conducted intensive research in light of the above-mentioned circumstances, and as a result have found that a positive electrode active material for lithium secondary batteries having lithium nickel manganese cobalt composite oxide particles and a coating portion coating at least a portion of the particle surfaces of the lithium nickel manganese cobalt composite oxide particles can be obtained by mixing a nickel source, a manganese source, a cobalt source, a lithium source, lithium molybdate, and optionally an M source to obtain a raw material mixture, and firing the raw material mixture at a predetermined temperature, and that a lithium secondary battery using the positive electrode active material for lithium secondary batteries has excellent cycle characteristics, and have completed the present invention.
[0010] That is, the present invention (1) relates to a compound represented by the following general formula (1): Li x Ni y Mnz Co t M p O 1+x (1) (In the formula, M represents one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. 0.98 ≦ x ≦ 1.20, y satisfies 0.30 ≦ y < 1.00, z satisfies 0 < z ≦ 0.50, t satisfies 0 < t ≦ 0.50, p satisfies 0 ≦ p ≦ 0.05, and y + z + t + p = 1.) A positive electrode active material for a lithium secondary battery, comprising lithium nickel manganese cobalt composite oxide particles represented by the formula and a coating portion that coats at least a part of the surface of the lithium nickel manganese cobalt composite oxide particles, wherein the coating portion contains Mo, and in the spectrum of O1s obtained by X-ray photoelectron spectroscopy of the surface of the coating portion, there is only one peak in the range of 525 eV or more and 535 eV or less. A positive electrode active material for a lithium secondary battery is provided.
[0011] Further, the present invention (2) provides the positive electrode active material for a lithium secondary battery according to (1), wherein in the spectra of Co2p and Mn3p obtained by X-ray photoelectron spectroscopy of the surface of the coating portion, peaks are not substantially detected. 1 / 2
[0012] Further, the present invention (3) provides a method for producing a positive electrode active material for a lithium secondary battery, which comprises firing a raw material mixture prepared by mixing a nickel source, a manganese source, a cobalt source, a lithium source, lithium molybdate, and an M source as needed.
[0013] Further, the present invention (4) provides the method for producing a positive electrode active material for a lithium secondary battery according to (3), wherein a composite compound containing nickel atoms, manganese atoms, and cobalt atoms is used as the nickel source, the manganese source, and the cobalt source.
[0014] Further, the present invention (5) provides a method for producing a positive electrode active material for a lithium secondary battery according to (3) or (4), characterized in that the lithium molybdate is Li2MoO4.
[0015] Further, the present invention (6) provides a method for producing a positive electrode active material for a lithium secondary battery according to any one of (3) to (5), characterized in that the firing is performed at 600 to 1000 °C.
[0016] Further, the present invention (7) provides a method for producing a positive electrode active material for a lithium secondary battery according to any one of (3) to (6), characterized in that the mixing amount of the lithium molybdate is such that the amount of Mo in terms of atoms is 0.01 to 5.00 mol% with respect to the total amount of Ni, Mn, Co, and M in terms of atoms in the nickel source, manganese source, cobalt source, and M source.
[0017] Further, the present invention (8) is such that the positive electrode active material for a lithium secondary battery is represented by the following general formula (1): Li x Ni y Mn z Co t M p O 1+x (1) (In the formula, M represents one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. 0.98 ≦ x ≦ 1.20, y satisfies 0.30 ≦ y < 1.00, z satisfies 0 < z ≦ 0.50, t satisfies 0 < t ≦ 0.50, p satisfies 0 ≦ p ≦ 0.05, and y + z + t + p = 1.) The present invention provides a method for producing a positive electrode active material for a lithium secondary battery according to any one of (3) to (7), characterized by comprising lithium nickel manganese cobalt composite oxide particles represented by the formula and a coating portion that coats at least a part of the particle surface of the lithium nickel manganese cobalt composite oxide particles.
[0018] The present invention (9) also provides a method for producing a positive electrode active material for a lithium secondary battery, comprising the step of mixing large particles having an average particle diameter of 7.5 to 30.0 μm obtained by any one of the production methods (3) to (8) with small particles having an average particle diameter of 0.5 to 7.5 μm obtained by any one of the production methods (3) to (8).
[0019] The present invention (10) also provides a lithium secondary battery using the positive electrode active material for lithium secondary batteries according to (1) or (2). Effect of the Invention
[0020] According to the present invention, it is possible to provide a positive electrode active material for lithium secondary batteries that can impart excellent cycle characteristics to lithium secondary batteries that use a lithium nickel manganese cobalt composite oxide as a positive electrode active material, an industrially advantageous method for producing the same, and a lithium secondary battery with excellent cycle characteristics. [Brief description of the drawings]
[0021] [Figure 1] 3 is an X-ray diffraction diagram of the positive electrode active material samples obtained in Example 2 and Comparative Example 1. [Diagram 2] FIG. 2 is a graph showing the change in the elemental amounts of Ni, Co, and Mo in the depth direction of the positive electrode active material sample obtained in Example 1. [Diagram 3] FIG. 4 is a graph showing changes in the amounts of Ni, Co, and Mo elements in the depth direction of the positive electrode active material sample obtained in Comparative Example 2. [Figure 4] FIG. 2 is a graph showing an O1s spectrum on the surface of a positive electrode active material sample obtained in Example 1. [Diagram 5] FIG. 2 is a diagram showing a spectrum of Li1s&Mn3p on the surface of the positive electrode active material sample obtained in Example 1. [Figure 6] FIG. 2 is a diagram showing a spectrum of Co2p1 / 2 on the surface of a positive electrode active material sample obtained in Example 1. [Figure 7] FIG. 13 is a graph showing an O1s spectrum on the surface of a positive electrode active material sample obtained in Comparative Example 2. [Figure 8]Figure showing the spectra of Li1s&Mn3p on the surface of the positive electrode active material sample obtained in Comparative Example 2. [Figure 9] Figure showing the spectra of Co2p1 / 2 on the surface of the positive electrode active material sample obtained in Comparative Example 2.
Embodiments for Carrying Out the Invention
[0022] Hereinafter, the present invention will be described based on preferred embodiments. The positive electrode active material for a lithium secondary battery of the present invention has the following general formula (1): Li x Ni y Mn z Co t M p O 1+x (1) (In the formula, M represents one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. 0.98 ≦ x ≦ 1.20, y represents 0.30 ≦ y < 1.00, z represents 0 < z ≦ 0.50, t represents 0 < t ≦ 0.50, p represents 0 ≦ p ≦ 0.05, and y + z + t + p = 1.) It is a positive electrode active material for a lithium secondary battery having lithium nickel manganese cobalt composite oxide particles represented by the formula and a coating portion that coats at least a part of the particle surface of the lithium nickel manganese cobalt composite oxide particles, the coating portion contains Mo, and in the spectrum of O1s obtained by X-ray photoelectron spectroscopy of the surface of the coating portion, there is only one peak existing in the range of 525 eV or more and 535 eV or less. It is a positive electrode active material for a lithium secondary battery characterized by this.
[0023] In the positive electrode active material for lithium secondary batteries of the present invention, at least a part of the particle surface of the lithium nickel manganese cobalt composite oxide particles represented by general formula (1) is covered with a coating portion containing Mo. In addition, in the positive electrode active material for lithium secondary batteries of the present invention, in an O1s spectrum obtained by X-ray photoelectron spectroscopy of the surface of the coating portion, there is only one peak present in the range of 525 eV to 535 eV. In other words, the positive electrode active material for a lithium secondary battery of the present invention is a composite particle comprising a lithium nickel manganese cobalt composite oxide particle represented by general formula (1) as a core particle, and a coating portion that coats the particle surface of the lithium nickel manganese cobalt composite oxide particle.
[0024] Therefore, the positive electrode active material for lithium secondary batteries of the present invention is distinguished from lithium nickel manganese cobalt composite oxide particles in which Mo is incorporated by solid solution in lithium nickel manganese cobalt composite oxide particles. The lithium nickel manganese cobalt composite oxide particles in which Mo is incorporated by solid solution in lithium nickel manganese cobalt composite oxide particles are basically composed of one type of lithium nickel manganese cobalt composite oxide, although the amount of Mo in solid solution varies depending on the depth position in the particle, that is, they are composed of only lithium nickel manganese cobalt composite oxide particles in which Mo is incorporated by solid solution in lithium nickel manganese cobalt composite oxide particles. On the other hand, the positive electrode active material for lithium secondary batteries of the present invention is a composite particle having a core particle and a coating portion containing Mo, in addition to the lithium nickel manganese cobalt composite oxide particle which is the core particle.
[0025] In the positive electrode active material for a lithium secondary battery of the present invention, the lithium nickel manganese cobalt composite oxide particle, which is the core particle, is a composite oxide containing lithium, nickel, manganese and cobalt, and is represented by the following general formula (1). Li x Ni y Mn z Co t M p O 1+x (1) (In the formula, M represents one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. 0.98 ≦ x ≦ 1.20, y satisfies 0.30 ≦ y < 1.00, z satisfies 0 < z ≦ 0.50, t satisfies 0 < t ≦ 0.50, p satisfies 0 ≦ p ≦ 0.05, and y + z + t + p = 1.)
[0026] In the general formula (1), x satisfies 0.98 ≦ x ≦ 1.20. In terms of achieving a high initial capacity, it is preferably 1.00 ≦ x ≦ 1.10. Also, in the general formula (1), y satisfies 0.30 ≦ y < 1.00. In terms of achieving both a favorable initial capacity and cycle characteristics, it is preferably 0.50 ≦ y ≦ 0.95, and particularly preferably 0.60 ≦ y ≦ 0.90. Further, in the general formula (1), z satisfies 0 < z ≦ 0.50. In terms of excellent safety, it is preferably 0.025 ≦ z ≦ 0.45. Also, t satisfies 0 < t ≦ 0.50. In terms of excellent safety, it is preferably 0.025 ≦ t ≦ 0.45. y + z + t + p = 1. y / z is preferably (y / z) > 1, particularly preferably (y / z) ≧ 1.5, and more preferably 3 ≦ (y / z) ≦ 38.
[0027] Also, M in the formula is a metal element that is incorporated into the lithium nickel manganese cobalt composite oxide represented by the general formula (1) as needed for the purpose of improving battery performance such as cycle characteristics and safety. Examples of M include one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. In the general formula (1), p satisfies 0 ≦ p ≦ 0.050, preferably 0.0001 ≦ p ≦ 0.045.
[0028] In the positive electrode active material for a lithium secondary battery of the present invention, the coating portion contains Mo, and in the O1s spectrum obtained by X-ray photoelectron spectroscopy of the surface of the coating portion, there is only one peak in the range of 525 eV to 535 eV. By having the coating portion, it is possible to suppress the elution of transition metals from the inside of the lithium nickel manganese cobalt composite oxide particles while maintaining lithium ion conductivity, and improve cycle characteristics.
[0029] The state of existence of Mo contained in the coating portion is unclear, but when the positive electrode active material for a lithium secondary battery of the present invention is mixed with water, stirred to form a slurry, filtered to obtain a filtrate, and measured by ICP atomic emission spectrometry, Mo is detected, and the amount of Mo detected is smaller than the theoretical amount of Mo charged. Therefore, the present inventors speculate that a part of Mo is present in the coating portion as a water-soluble compound containing Mo, and the remaining Mo is present in the form of a solid solution inside the particles of the lithium nickel manganese cobalt composite oxide and / or is present in the coating portion as a poorly water-soluble compound containing Mo.
[0030] In the positive electrode active material for a lithium secondary battery of the present invention, the amount of Mo (A) resulting from the water-soluble compound containing Mo present in the coating portion is determined by stirring and mixing 5 g of a sample of the positive electrode active material for a lithium secondary battery in 100 ml of pure water at room temperature for 5 minutes, filtering the mixture, transferring 1 ml of the filtrate to a measuring flask, adding 1 ml of nitric acid, and diluting the mixture with pure water to make 100 ml, and measuring the amount of Mo by ICP atomic emission spectrometry. The amount of Mo (D) that is considered to be present as a solid solution inside the lithium nickel manganese cobalt composite oxide particles and / or as a poorly water-soluble compound containing Mo in the coating portion is calculated by the following formula (1): D=BA (1) (A is the amount of Mo (mass %) attributed to water-soluble compounds in the sample, determined by stirring and mixing 5 g of sample in 100 ml of pure water at room temperature for 5 minutes, filtering, transferring 1 ml of the filtrate to a measuring flask, adding 1 ml of nitric acid, and diluting the solution to 100 ml with pure water, and measuring the solution by ICP atomic emission spectrometry. B is the total Mo content (mass %) in the sample, determined by adding approximately 10 ml of pure water and 4 ml of aqua regia to 0.5 g of sample, heating to boiling to completely dissolve the sample, transferring to a measuring flask and diluting the solution to 100 ml with pure water, transferring 1 ml of the solution to another measuring flask and diluting the solution to 100 ml with pure water, and then measuring the solution by ICP atomic emission spectrometry.)
[0031] Co2p obtained by X-ray photoelectron spectroscopy of the surface of the coating 1 / 2 In other words, Co and Mn are substantially absent at least on the outermost surface of the coating portion. In addition, Co2p 1 / 2 In the spectrum of Co2p, the peak is substantially not detected. 1 / 2 In the spectrum of Mn3p, no peak exists in the range of 790 eV to 800 eV, that is, the peak in this range is below the lower detection limit of the analyzer. In addition, "substantially no peak is detected in the spectrum of Mn3p" means that no peak exists in the range of 45 eV to 52 eV in the spectrum of Mn3p, that is, the peak in this range is below the lower detection limit of the analyzer. In the present invention, the spectrum of Mn3p is obtained as the spectrum of Li1s&Mn3p including the spectrum of Li1s (see FIG. 5), but the spectrum of Mn3p is the spectrum in the range of 45 eV to 52 eV in the spectrum of Li1s&Mn3p, and the spectrum of Li1s is the spectrum in the range of 52 eV to 58 eV in the spectrum of Li1s&Mn3p.
[0032] The coating portion may cover the entire or a part of the particle surface of the lithium nickel manganese cobalt composite oxide particle. Here, coating a part of the particle surface refers to a state in which the particle surface has a part where the surface of the lithium nickel manganese composite oxide particle to be coated is exposed in addition to the coating portion.
[0033] The thickness of the coating portion is preferably 0.5 nm to 150 nm, more preferably 1 nm to 120 nm, more preferably 1.5 nm to 100 nm, and particularly preferably 2 nm to 90 nm. By having the thickness of the coating portion within the above range, it is possible to suppress the elution of transition metals from the inside of the lithium nickel manganese cobalt composite oxide particles while maintaining lithium ion conductivity, and improve cycle characteristics.
[0034] The average particle size of the positive electrode active material for lithium secondary batteries of the present invention is 0.50 to 30.0 μm, preferably 1.0 to 25.0 μm, and particularly preferably 1.5 to 20.0 μm, as a particle size at 50% volume (D50) determined by a laser diffraction / scattering method. The BET specific surface area of the positive electrode active material for lithium secondary batteries obtained by the method for producing a positive electrode active material for lithium secondary batteries of the present invention is preferably 0.05 to 2.00 m. 2 / g, particularly preferably 0.15 to 1.00 m 2 When the average particle size or BET specific surface area of the positive electrode active material for lithium secondary batteries obtained by carrying out the method for producing a positive electrode active material for lithium secondary batteries of the present invention is within the above-mentioned range, the preparation and coating properties of the positive electrode mixture become easy, and furthermore, an electrode with high packing properties can be obtained.
[0035] The method for producing a positive electrode active material for a lithium secondary battery of the present invention is characterized by calcining a raw material mixture prepared by mixing a nickel source, a manganese source, a cobalt source, a lithium source, lithium molybdate, and, if necessary, an M source. In other words, the method for producing a positive electrode active material for a lithium secondary battery of the present invention basically comprises the following raw material mixture preparation step and firing step, and thereby makes it possible to industrially advantageously obtain a positive electrode active material for a lithium secondary battery that can be imparted with excellent cycle characteristics. Raw material mixture preparation process: nickel source, manganese source, cobalt source, lithium source, molybdenum A step of mixing the lithium oxide and, if necessary, the M source to prepare a raw material mixture. Firing step: a step of firing the raw material mixture prepared in the raw material mixture preparation step to obtain a positive electrode active material for a lithium secondary battery.
[0036] (Raw material mixture adjustment process) The raw material mixture preparation step is a step of preparing a raw material mixture by mixing a nickel source, a manganese source, a cobalt source, a lithium source, and lithium molybdate as essential raw materials, and further mixing an M source as necessary. M is one or more metallic elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K.
[0037] In the raw material mixture preparation step, the nickel source, manganese source, cobalt source and M source may be, for example, hydroxides, oxides, carbonates, nitrates, sulfates, organic acid salts and the like of nickel, manganese, cobalt and the M element. The nickel source, manganese source, cobalt source and the M source added as necessary have an average particle size of 0.50 to 30.0 μm, preferably 1.0 to 25.0 μm, in terms of the particle size at 50% volume (D50) determined by a laser diffraction / scattering method.
[0038] In the raw material mixture preparation step, the nickel source, the manganese source, and the cobalt source may be a composite compound containing nickel atoms, manganese atoms, and cobalt atoms. Examples of the composite compound containing nickel atoms, manganese atoms, and cobalt atoms include composite oxides, composite hydroxides, composite oxyhydroxides, and composite carbonates containing nickel atoms, manganese atoms, and cobalt atoms. Among these, the nickel source, the manganese source, and the cobalt source are preferably composite hydroxides containing nickel atoms, manganese atoms, and cobalt atoms in that they provide higher cycle characteristics.
[0039] In the raw material mixture preparation step, the nickel source, the manganese source and the cobalt source may be mixed composite particles of a nickel compound, a manganese compound and a cobalt compound.
[0040] A known method can be used to prepare the composite compound containing nickel atoms, manganese atoms, and cobalt atoms. For example, in the case of a composite hydroxide, it can be prepared by a coprecipitation method. Specifically, a composite hydroxide can be coprecipitated by mixing an aqueous solution containing a predetermined amount of nickel atoms, cobalt atoms, and manganese atoms, an aqueous solution of a complexing agent, and an aqueous solution of an alkali (see JP-A-10-81521, JP-A-10-81520, JP-A-10-29820, JP-A-2002-201028, etc.). For example, in the case of a composite carbonate, a method of reacting a solution (Liquid A) containing nickel ions, manganese ions, and cobalt ions with a solution (Liquid B) containing carbonate ions or hydrogen carbonate ions in a reaction vessel (Japanese Patent Laid-Open No. 2009-179545) can be mentioned, or a method of reacting a solution (Liquid A) containing a nickel salt, manganese salt, and cobalt salt with a solution (Liquid B) containing a metal carbonate or metal hydrogen carbonate can be added to a solution (Liquid C) containing the same anion as the anion of the nickel salt, manganese salt, and cobalt salt in Liquid A and the same anion as the anion of the metal carbonate or metal hydrogen carbonate in Liquid B (Japanese Patent Laid-Open No. 2009-179544). The composite compound containing nickel atoms, manganese atoms, and cobalt atoms may be a commercially available product.
[0041] The mixed composite particles containing a nickel compound, a manganese compound and a cobalt compound can be prepared by a known method. For example, a slurry containing nickel compound particles, manganese compound particles, and cobalt compound particles can be pulverized using a bead mill or the like, and then spray-dried (JP Patent Publication No. 2012-206929), to obtain a mixed composite containing a nickel compound, a manganese compound, and a cobalt compound. The mixed composite particles containing a nickel compound, a manganese compound, and a cobalt compound may be a commercially available product.
[0042] In the raw material mixture preparation step, the composite compound containing nickel atoms, manganese atoms and cobalt atoms or the mixed composite particles containing a nickel compound, a manganese compound and a cobalt compound as the nickel source, manganese source and cobalt source have an average particle size of 0.50 to 100 μm, preferably 1.0 to 80.0 μm, as determined by a laser diffraction / scattering method as a 50% volume-integrated particle size (D50).
[0043] In the raw material mixture preparation step, the mixing ratio of the nickel source, manganese source, cobalt source and M source is appropriately selected depending on the composition ratio of nickel, manganese, cobalt and M in the lithium nickel manganese cobalt composite oxide to be produced, but is preferably selected from the following general formula (1): Li x Ni y Mn z Co t M p O 1+x (1) (In the formula, M represents one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. 0.98 ≤ x ≤ 1.20, y satisfies 0.30 ≤ y < 1.00, z satisfies 0 < z ≤ 0.50, t satisfies 0 < t ≤ 0.50, p satisfies 0 ≤ p ≤ 0.05, and y + z + t + p = 1.) This is the mixing ratio to form a lithium nickel manganese cobalt composite oxide represented by
[0044] In the raw material mixture preparation step, the lithium source is not particularly limited as long as it is a lithium compound usually used as a raw material for manufacturing a lithium cobalt composite oxide. However, lithium compounds other than lithium molybdate, such as lithium oxides, hydroxides, carbonates, nitrates, sulfates, and organic acid salts, are preferred.)
[0045] In the raw material mixture preparation step, the average particle size of the lithium source is not particularly limited, and generally available ones can be used. For example, particle sizes in the range of 1 to 100 μm are common.)
[0046] In the raw material mixture preparation step, the mixing ratio of the lithium source is preferably such that the molar ratio of Li atoms to the total number of moles of Ni atoms, Mn atoms, Co atoms, and M atoms in terms of atoms in the nickel source, manganese source, cobalt source, and M source (Li / (Ni + Mn + Co + M)) is 0.98 to 1.20, and particularly preferably 1.00 to 1.10. When the mixing ratio of the lithium source is within the above range, it is possible to increase the amount of lithium involved in the battery reaction while suppressing the amount of lithium present as residual alkali in the positive electrode active material for a lithium secondary battery.)
[0047] In the raw material mixture preparation step, examples of lithium molybdate include Li2MoO4, Li4MoO5, Li2Mo2O7, Li4Mo5O 17 , Li2Mo3O 10 , Li2Mo4O 13Or a mixture of these may be used, but Li2MoO4 is preferred in that the particle size can be easily adjusted by pulverization.
[0048] In the raw material mixture preparation step, the average particle size of lithium molybdate is preferably 100.0 μm or less, more preferably 0.01 to 80.0 μm, as a particle size at 50% volume (D50) determined by a laser diffraction / scattering method using ethanol as a solvent. When the average particle size of lithium molybdate is within the above range, it becomes possible to uniformly mix lithium molybdate into the raw material mixture.
[0049] The lithium molybdate may be an aggregate in which primary particles are aggregated to form secondary particles. When the lithium molybdate is an aggregate, the primary particle diameter of the lithium molybdate is preferably 80.0 μm or less, and more preferably 0.001 to 60.0 μm, as determined from a scanning electron microscope (SEM) photograph, from the viewpoint of uniformly mixing the lithium molybdate in the raw material mixture.
[0050] The average particle size of the primary particles was determined by randomly extracting 30 particles from SEM observation, measuring the short diameter and long diameter of each particle, calculating half the sum of the two, and averaging the measurements of the 30 particles to obtain the average particle size.
[0051] In the raw material mixture preparation step, the amount of lithium molybdate mixed is an amount such that the amount (mol) of Mo in atomic terms is 0.01 to 5.00 mol %, preferably 0.02 to 4.50 mol %, relative to the total amount (mol) of Ni, Mn, Co, and M in atomic terms in the nickel source, manganese source, cobalt source, and M source. By mixing an amount of lithium molybdate in the above range, it becomes possible to achieve both initial capacity and cycle characteristics within preferred ranges.
[0052] In the raw material mixture preparation step, the nickel source, the manganese source, the cobalt source, the lithium source, the lithium molybdate, and the M source can be mixed by either a dry method or a wet method, but the dry method is preferred because of ease of production.
[0053] In the case of dry mixing, it is preferable to use a mechanical means so that the raw materials are mixed uniformly. Examples of mixing devices include high-speed mixers, super mixers, turbosphere mixers, Eirich mixers, Henschel mixers, Nauta mixers, ribbon blenders, V-type mixers, conical blenders, jet mills, cosmomixers, paint shakers, bead mills, ball mills, etc. At the laboratory level, household mixers and laboratory mills are sufficient.
[0054] In the case of wet mixing, it is preferable to use a media mill as a mixing device, since it is possible to prepare a slurry in which each raw material is uniformly dispersed. In addition, it is preferable to spray-dry the slurry after the mixing process, from the viewpoint of obtaining a raw material mixture with excellent reactivity and in which each raw material is uniformly dispersed.
[0055] (Firing process) The calcination step is a step of calcining the raw material mixture prepared in the raw material mixture preparation step. By carrying out this calcination, a positive electrode active material for lithium secondary batteries can be obtained.
[0056] In the calcination step, the calcination temperature is 600 to 1000° C., preferably 650 to 950° C. The reason for this is that if the calcination temperature is less than 600° C., the reaction is insufficient and a large amount of unreacted lithium tends to remain, whereas if the calcination temperature exceeds 1000° C., the lithium nickel manganese cobalt composite oxide that has been produced tends to decompose.
[0057] In the calcination step, the calcination time is not critical, and a calcination time of 3 hours or more, preferably 5 to 30 hours, can provide a positive electrode active material for a lithium secondary battery with satisfactory performance. The calcination atmosphere is preferably an atmospheric atmosphere such as air or oxygen gas.
[0058] Also, in the firing process, the firing may be performed in multiple stages. By firing in multiple stages, a cathode active material for a lithium secondary battery that can impart even more excellent cycle characteristics can be obtained. When firing in multiple stages, after firing at 600 to 800°C, preferably 650 to 800°C for 1 to 10 hours, without cooling, the temperature is further increased to 800 to 1000°C, preferably 800 to 950°C so as to reach a higher temperature, and it is preferably fired at that temperature for 5 to 30 hours.
[0059] In the method for manufacturing a cathode active material for a lithium secondary battery of the present invention, after the firing process, pulverization, classification, granulation, etc. may be performed as necessary.
[0060] The cathode active material for a lithium secondary battery obtained by performing the method for manufacturing a cathode active material for a lithium secondary battery of the present invention has the following general formula (1): Li x Ni y Mn z Co t M p O 1+x (1) (In the formula, M represents one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. 0.98 ≦ x ≦ 1.20, y is 0.30 ≦ y < 1.00, z is 0 < z ≦ 0.50, t is 0 < t ≦ 0.50, p is 0 ≦ p ≦ 0.05, and y + z + t + p = 1.) It has lithium nickel manganese cobalt composite oxide particles represented by the formula and a coating portion that coats at least a part of the particle surface of the lithium nickel manganese cobalt composite oxide particles. Further, the coating portion contains Mo, and in the spectrum of O1s obtained by X-ray photoelectron spectroscopy of the surface of the coating portion, there is only one peak in the range of 525 eV or more and 535 eV or less.
[0061] In the formula of general formula (1), x satisfies 0.98 ≦ x ≦ 1.20. Preferably, x satisfies 1.00 ≦ x ≦ 1.10 in terms of the initial capacity being high. Also, in the formula of general formula (1), y satisfies 0.30 ≦ y < 1.00. Preferably, y satisfies 0.50 ≦ y ≦ 0.95 in terms of both the initial capacity and cycle characteristics being in a preferable range, and particularly preferably 0.60 ≦ y ≦ 0.90. Further, in the formula of general formula (1), z satisfies 0 < z ≦ 0.50. Preferably, z satisfies 0.025 ≦ z ≦ 0.45 in terms of excellent safety. Also, t satisfies 0 < t ≦ 0.50. Preferably, t satisfies 0.025 ≦ t ≦ 0.45 in terms of excellent safety. y + z + t + p = 1. Preferably, (y / z) > 1, particularly preferably (y / z) ≧ 1.5, and more preferably 3 ≦ (y / z) ≦ 38.
[0062] In the formula, M is a metal element that is incorporated into the lithium nickel manganese cobalt composite oxide represented by general formula (1) as needed for the purpose of improving battery performance such as cycle characteristics and safety. Examples of M include one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. In the formula of general formula (1), p satisfies 0 ≦ p ≦ 0.050, preferably 0.0001 ≦ p ≦ 0.045.
[0063] In the method for producing a positive electrode active material for a lithium secondary battery of the present invention, by mixing lithium molybdate not with a lithium nickel manganese cobalt composite oxide but into the raw material before producing the lithium nickel manganese cobalt composite oxide, a positive electrode active material for a lithium secondary battery with excellent cycle characteristics can be obtained. And in the method for producing a positive electrode active material for a lithium secondary battery of the present invention, by using a composite compound containing nickel atoms, manganese atoms, and cobalt atoms as the raw material nickel source, manganese source, and cobalt source, the effect of obtaining a positive electrode active material for a lithium secondary battery with excellent cycle characteristics is enhanced.
[0064] In the method for producing the positive electrode active material for lithium secondary batteries of the present invention, for example, large particles having an average particle size of 7.5 to 30.0 μm, preferably 8.0 to 25.0 μm, particularly preferably 8.5 to 20.0 μm, and small particles smaller than the large particles, that is, small particles having an average particle size of 0.5 to 7.5 μm, preferably 1.0 to 7.0 μm, particularly preferably 1.5 to 6.5 μm, may be separately produced, and then the obtained large particles and small particles may be mixed at a predetermined mixing ratio. The positive electrode active material for lithium secondary batteries obtained by performing the step of mixing the large particles and the small particles at a predetermined mixing ratio can be a positive electrode active material for lithium secondary batteries that can provide excellent cycle characteristics while further increasing the discharge capacity per volume.
[0065] The mixing ratio of the large particles to the small particles is preferably 7:13 to 19:1 by mass, and more preferably 1:1 to 9:1 by mass. 2 The compression density when compressed is 2.7g / cm 3 or more, preferably 2.8 to 3.3 g / cm 3 , particularly preferably 2.9 to 3.3 g / cm 3 This is preferable from the viewpoint of further improving the discharge capacity per volume.
[0066] As a method for producing large particles, for example, in the above-mentioned raw material mixture preparation step, composite compounds containing nickel atoms, manganese atoms, and cobalt atoms, each having a volume-integrated 50% particle diameter (D50) of 7.5 to 100 μm, preferably 8.0 to 80 μm, as the nickel source, manganese source, and cobalt source determined by a laser diffraction / scattering method, are used, and then the above-mentioned firing step is carried out, thereby obtaining large particles. As for a method for producing small particles, for example, in the above-mentioned raw material mixture preparation step, composite compounds containing nickel atoms, manganese atoms, and cobalt atoms, each having a 50% volume cumulative particle diameter (D50) of 0.5 to 7.5 μm, preferably 1.0 to 7.0 μm, as the nickel source, manganese source, and cobalt source determined by a laser diffraction / scattering method, are used, and then the above-mentioned firing step is carried out, thereby obtaining small particles.
[0067] The positive electrode active material for lithium secondary batteries obtained by the method for producing a positive electrode active material for lithium secondary batteries of the present invention is useful in that it can impart excellent cycle characteristics when used as a positive electrode active material for lithium secondary batteries. EXAMPLES
[0068] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.
[0069] (Examples 1 to 6) (Raw material mixture preparation process) Lithium carbonate (average particle size 5.7 μm), nickel manganese cobalt composite hydroxide (Ni:Mn:Co=6:2:2 (molar ratio), average particle size 3.8 μm or 12.1 μm), and lithium molybdate (Li2MoO4, average particle size 13.4 μm) were weighed out and thoroughly mixed in a household mixer to obtain a raw material mixture in which the molar ratio (feed ratio) of Li / (Ni+Mn+Co) and the mixed amount of lithium molybdate were values shown in Table 1. Note that, for the nickel manganese cobalt composite hydroxide used in Examples 1 to 4, a commercially available product with an average particle size of 3.8 μm and an average particle size of 12.1 μm was used in Examples 5 and 6. (Firing process) The resulting raw material mixture was then sintered in an alumina pot at 700°C for 2 hours, followed by sintering at 850°C for 10 hours in an air atmosphere. After sintering, the sintered product was crushed and classified to obtain a positive electrode active material sample. The positive electrode active material sample obtained in Example 2 was measured by X-ray diffraction (XRD), and a diffraction peak derived from the lithium nickel manganese cobalt composite oxide was confirmed (see (a) in Figure 1).
[0070] Comparative Example 1 (Raw material mixture preparation process) Lithium carbonate (average particle size 5.7 μm) and nickel manganese cobalt composite hydroxide (Ni:Mn:Co=6:2:2 (molar ratio), average particle size 3.8 μm) were weighed out and thoroughly mixed in a household mixer to obtain a raw material mixture having a Li / (Ni+Mn+Co) molar ratio (feed ratio) shown in Table 1. The nickel manganese cobalt composite hydroxide used was commercially available. (Firing process) The resulting raw material mixture was then sintered in an alumina pot at 700°C for 2 hours, and then at 850°C for 10 hours in an air atmosphere. After sintering, the sintered product was crushed and classified to obtain a positive electrode active material sample. The obtained positive electrode active material sample was measured by XRD, and a diffraction peak derived from the lithium nickel manganese cobalt composite oxide was confirmed (see (b) in Figure 1). In addition, the obtained positive electrode active material sample contained secondary aggregated spherical lithium nickel manganese cobalt composite oxide (LiNi 0.6 Mn 0.2 Co 0.2 O2).
[0071] Comparative Example 2 The lithium nickel manganese cobalt composite oxide (LiNi 0.6 Mn 0.2 Co 0.2 Lithium molybdate (Li2MoO4, average particle size 13.4μm) was added to the lithium nickel manganese cobalt composite oxide (Li2MoO2) and mixed thoroughly in a laboratory mill to obtain a mixture containing lithium molybdate. The resulting mixture was then fired at 850°C for 5 hours. After firing, the fired product was crushed and classified to obtain a positive electrode active material sample.
[0072] For the positive electrode active material samples obtained in the examples and comparative examples, the following physical properties were measured, and the results are shown in Table 1. <Average particle diameter> It was determined by the laser diffraction / scattering method. <BET specific surface area> It was determined by the BET method. <Pressed density> 2.25 g of the positive electrode active material sample was weighed and put into a biaxial shaper with a diameter of 1.5 cm, and the pressure of 0.65 tonf / cm 2 was applied for 1 minute using a press machine, the height of the compressed product was measured, and the pressed density of the positive electrode active material sample was calculated from the apparent volume of the compressed product calculated from the height and the mass of the weighed positive electrode active material sample.
[0073]
Table 1
[0074] Regarding ※1 in Table 1, the mixing amount of lithium molybdate was calculated as the percentage of the amount (mol) of Mo in terms of atoms to the total amount (mol) of Ni, Mn, and Co in terms of atoms.
[0075] <Measurement of Mo amount> Regarding the positive electrode active material samples obtained in the examples, the amount of Mo (D) considered to exist as Mo dissolved in the particles of the lithium nickel manganese cobalt composite oxide and / or as a water-insoluble compound containing Mo in the coating part was calculated by the following formula. The results are shown in Table 2. D = B - A (A is the amount of Mo (mass %) attributable to water-soluble compounds in the sample determined by measuring, by ICP emission spectrometry, a solution obtained by stirring and mixing 5 g of the positive electrode active material sample with 100 ml of pure water at room temperature for 5 minutes, filtering, transferring 1 ml of the filtrate to a volumetric flask, adding 1 ml of nitric acid, and making up to 100 ml with pure water. B is the total Mo content (mass %) in the sample determined by measuring, by ICP emission spectrometry, a solution obtained by transferring 1 ml of a solution obtained by adding approximately 10 ml of pure water and 4 ml of aqua regia to 0.5 g of the sample, heating to boiling to completely dissolve the sample, transferring to a volumetric flask, making up to 100 ml with pure water, and then transferring 1 ml of the solution to another volumetric flask and making up to 100 ml with pure water.)
[0076]
Table 2
[0077] The "total Mo content" in Table 2 is the total Mo content (mass %) in the sample determined by measuring, by ICP emission spectrometry, a solution obtained by transferring 1 ml of a solution obtained by adding approximately 10 ml of pure water and 4 ml of aqua regia to 0.5 g of the positive electrode active material sample, heating to boiling to completely dissolve the sample, transferring to a volumetric flask, making up to 100 ml with pure water, and then transferring 1 ml of the solution to another volumetric flask and making up to 100 ml with pure water.)
[0078] <X-ray Photoelectron Spectroscopy> For the positive electrode active material samples obtained in Example 1 and Comparative Example 2, the following depth profile analysis and surface analysis were performed by X-ray photoelectron spectroscopy (apparatus name: PHI 5000 VersaProbe III manufactured by ULVAC-PHI, Inc.). · Depth profile analysis The surface of the positive electrode active material sample was etched with argon in the depth direction, and Ni peaks, Co peaks, and Mo peaks were measured in the depth direction. Figures 2 and 3 show the changes in "the amount of Ni element (at%) relative to the total of Ni, Co, and Mo ((Ni / (Ni+Co+Mo))×100)", "the amount of Co element (at%) relative to the total of Ni, Co, and Mo ((Co / (Ni+Co+Mo))×100)", and "the amount of Mo element (at%) relative to the total of Ni, Co, and Mo ((Mo / (Ni+Co+Mo))×100)" in the depth direction of the positive electrode active material samples obtained in Example 1 and Comparative Example 2, respectively. The etching conditions are as follows. X-ray source: Monochromatic AlKα radiation Ion species: Ar + Acceleration voltage: 1 kV Sputtering rate: 1.23 nm / min (SiO2 equivalent) Measurement element orbitals: Ni:2p 3 / 2 Co:2p 1 / 2 Mo:3d ·Surface analysis Photoelectron spectra of O, Li, Mn, and Co on the surface of the positive electrode active material sample were measured. FIGS. 4, 5, and 6 show the photoelectron spectrum of O (O1s spectrum), the photoelectron spectrum of Li and Mn (Li1s & Mn3p spectrum), and the photoelectron spectrum of Co (Co2p 1 / 2 7, 8 and 9 show the O1s spectrum, Li1s & Mn3p spectrum and Co2p spectrum on the surface of the positive electrode active material sample obtained in Comparative Example 2. 1 / 2 The spectrum of
[0079] 2 and 3, it was confirmed that the amount of Ni element near the surface of the positive electrode active material sample was high but the amount of Co element was low in Example 1, and the amount of Ni and Co elements near the surface of the positive electrode active material sample was high in Comparative Example 2. Therefore, the inventors speculate that the positive electrode active material sample obtained in Example 1 has a coating portion with a thickness of about 30 nm, in which Mo is present, while the positive electrode active material sample obtained in Comparative Example 2 does not have a coating portion containing Mo, and Mo is present as a solid solution in the lithium nickel manganese composite oxide particles near the surface of the positive electrode active material sample.
[0080] Comparing FIG. 4 with FIG. 7, it was confirmed that the former has only one peak (near 532 eV) in the range of 525 eV to 535 eV, whereas the latter has two peaks (near 529 eV and 532 eV) in the same range. In addition, comparing Figures 5 and 8, in the former, the Mn3p spectrum does not have a peak in the range of 45 eV to 52 eV, which is below the detection limit, but in the latter, a peak is present in the range of 45 eV to 52 eV. In both cases, it was confirmed that the Li1s spectrum has a peak in the range of 52 eV to 58 eV. Also, comparing Figures 6 and 9, in the former, Co2p 1 / 2 In the spectrum of the first one, there is no peak in the range of 790 eV to 800 eV, which is below the detection limit, but in the spectrum of the second one, it was confirmed that there is a peak in the range of 790 eV to 800 eV.
[0081] The battery performance test was carried out as follows. <Preparation of lithium secondary battery 1> A positive electrode agent was prepared by mixing 94% by mass of the positive electrode active material samples obtained in the Examples and Comparative Examples, 3% by mass of graphite powder, and 3% by mass of polyvinylidene fluoride, and this was dispersed in N-methyl-2-pyrrolidinone to prepare a kneaded paste. The kneaded paste was applied to an aluminum foil, dried, pressed, and punched into a disk with a diameter of 15 mm to obtain a positive electrode plate.
[0082] Using this positive electrode plate, a coin-type lithium secondary battery was produced using each component such as a separator, negative electrode, positive electrode, current collector, mounting metal fittings, external terminals, and electrolyte, etc. Metallic lithium foil was used for the negative electrode, and 1 mole of LiPF6 dissolved in 1 liter of a 1:1 mixture of ethylene carbonate and methyl ethyl carbonate was used for the electrolyte.
[0083] <Battery performance evaluation 1> The coin-type lithium secondary batteries thus fabricated were then operated at room temperature under the following test conditions, and the following battery performance evaluations were performed. The results are shown in Table 3. (1) Test conditions for cycle characteristic evaluation First, the battery was charged to 4.3 V at 0.5 C over 2 hours, and then constant current / constant voltage charging (CCCV charging) was performed to hold the voltage at 4.3 V for 3 hours. Then, the battery was charged and discharged at a constant current (CC discharge) of 0.2 C or 1.0 C to 2.7 V. This cycle was repeated for a total of 30 cycles, and the discharge capacity was measured after each cycle. The battery was CC discharged at 0.2 C for the 1st, 2nd, 10th, 20th, and 30th cycles, and at 1.0 C for the other cycles. (2) Initial charge capacity, initial discharge capacity (per weight of active material) The charge capacity and discharge capacity in the first cycle in the cycle characteristic evaluation were defined as the initial charge capacity and the initial discharge capacity. (3) Discharge capacity at 30th cycle (per weight of active material) The discharge capacity at the 30th cycle in the cycle characteristic evaluation was defined as the 30th cycle discharge capacity. (4) Capacity maintenance rate The capacity retention rate was calculated from the discharge capacity (per active material weight) at the 1st cycle and the 30th cycle in the cycle characteristic evaluation according to the following formula. Capacity retention rate (%) = (discharge capacity at 30th cycle / discharge capacity at 1st cycle) x 100 (5) Energy density maintenance rate The energy density retention rate was calculated from the Wh capacity (per active material weight) during discharge in each of the 1st and 30th cycles in the cycle characteristic evaluation, using the following formula. Energy density retention rate (%) = (30th cycle discharge Wh capacity / 1st cycle discharge Wh capacity) x 100
[0084] [Table 3]
[0085] It can be seen from Table 3 that the lithium secondary batteries using the positive electrode active material samples obtained in Examples 1 to 6 had improved capacity retention rates and energy density retention rates compared to the lithium secondary battery using the positive electrode active material sample obtained in Comparative Example 1. In other words, it was confirmed that the lithium secondary batteries using the positive electrode active material sample having a coating portion containing Mo have excellent cycle characteristics. It is also found that the lithium secondary batteries using the positive electrode active material samples obtained in Examples 1 to 6 have improved capacity retention rate and energy density retention rate compared to the lithium secondary battery using the positive electrode active material sample obtained in Comparative Example 2. That is, it was confirmed that a lithium secondary battery using a positive electrode active material sample obtained by mixing lithium molybdate with raw materials before producing a lithium nickel manganese cobalt composite oxide to obtain a raw material mixture and firing the raw material mixture at a predetermined temperature has superior cycle characteristics compared to a lithium secondary battery using a positive electrode active material sample obtained by adding lithium molybdate to a lithium nickel manganese cobalt composite oxide, mixing them, and firing them.
[0086] <Preparation of lithium secondary battery 2> The positive electrode active material samples obtained in Examples 3 to 6 were thoroughly mixed in a household mixer to prepare mixtures having the compositions shown in Table 4, which were used as positive electrode active material samples. In addition, the pressed densities of the obtained positive electrode active material samples were measured, and the results are shown in Table 4.
[0087] [Table 4]
[0088] A positive electrode material was prepared by mixing 94% by mass of the positive electrode active material sample, 3% by mass of graphite powder, and 3% by mass of polyvinylidene fluoride, and this was dispersed in N-methyl-2-pyrrolidinone to prepare a kneaded paste. The kneaded paste was applied to an aluminum foil, dried, pressed, and punched into a disk with a diameter of 15 mm to obtain a positive electrode plate.
[0089] Using this positive electrode plate, a coin-type lithium secondary battery was produced using each component such as a separator, negative electrode, positive electrode, current collector, mounting metal fittings, external terminals, and electrolyte, etc. Metallic lithium foil was used for the negative electrode, and 1 mole of LiPF6 dissolved in 1 liter of a 1:1 mixture of ethylene carbonate and methyl ethyl carbonate was used for the electrolyte.
[0090] <Battery performance evaluation 2> Next, the prepared coin-type lithium secondary battery was operated at room temperature under the following test conditions, and the cycle characteristics, initial charge capacity, initial discharge capacity (per active material weight), 30th cycle discharge capacity (per active material weight), capacity retention rate, and energy density retention rate were evaluated in the same manner as in Battery Performance Evaluation 1, and further the following battery performance was evaluated. The results are shown in Table 5. (6) Discharge capacity per volume The discharge capacity per volume was calculated from the initial discharge capacity, the electrode density, and the ratio of the amount of active material in the coating agent according to the following formula. Discharge capacity per volume (mAh / cm 3 )=Initial discharge capacity (mAh / g) × Electrode density (g / cm 3 ) x 0.94 (proportion of active material in coating agent) The electrode density was calculated by measuring the mass and thickness of the electrode prepared from the measurement sample, and subtracting the thickness and mass of the current collector from the mass and thickness to obtain the density of the positive electrode material. The positive electrode material was a mixture of 94 mass % of the positive electrode active material sample, 3 mass % of graphite powder, and 3 mass % of polyvinylidene fluoride, and the pressing pressure during electrode preparation was 0.38 ton / cm in linear pressure.
[0091] [Table 5]
[0092] From Table 5, it was confirmed that Mixtures 1 and 2, which are mixtures of a positive electrode active material sample of large particles having a coating portion containing Mo and a positive electrode active material sample of small particles having a coating portion containing Mo, are positive electrode active materials for lithium secondary batteries that can increase the discharge capacity per volume while imparting excellent cycle characteristics.
Claims
1. The following general formula (1): Li x Ni y Mn z Co t M p O 1+x (1) (In the formula, M represents one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. 0.98≦x≦1.20, y represents 0.30≦y<1.00, z represents 0<z≦0.50, t represents 0<t≦0.50, p represents 0≦p≦0.05, and y+z+t+p=1.) and a coating portion that coats at least a part of the particle surface of the lithium nickel manganese cobalt composite oxide particle, The coating portion includes Mo, A positive electrode active material for a lithium secondary battery, characterized in that in an O1s spectrum obtained by X-ray photoelectron spectroscopy of the surface of the coating portion, there is only one peak present in the range of 525 eV or more and 535 eV or less.
2. The surface of the coating is analyzed by X-ray photoelectron spectroscopy. 1/2 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein substantially no peak is detected in the spectrum of Mn3p and the spectrum of Mn3p.
3. A method for producing a positive electrode active material for a lithium secondary battery, comprising calcining a raw material mixture prepared by mixing a nickel source, a manganese source, a cobalt source, a lithium source, lithium molybdate, and optionally an M source.
4. 4. The method for producing a positive electrode active material for a lithium secondary battery according to claim 3, wherein composite compounds containing nickel atoms, manganese atoms and cobalt atoms are used as the nickel source, the manganese source and the cobalt source.
5. The lithium molybdate is Li 2 MoO 4 5. The method for producing a positive electrode active material for a lithium secondary battery according to claim 3, wherein
6. 5. The method for producing a positive electrode active material for a lithium secondary battery according to claim 3, wherein the calcination is carried out at a temperature of 600 to 1000° C.
7. 5. The method for producing a positive electrode active material for a lithium secondary battery according to claim 3, wherein the amount of lithium molybdate mixed is an amount such that the amount of Mo in atomic terms is 0.01 to 5.00 mol % relative to the total amounts of Ni, Mn, Co, and M in atomic terms in the nickel source, manganese source, cobalt source, and M source.
8. The positive electrode active material for a lithium secondary battery is represented by the following general formula (1): Li x Ni y Mn z Co t M p O 1+x (1) (In the formula, M represents one or more metal elements selected from Mg, Al, Ti, Zr, Cu, Fe, Sr, Ca, V, Mo, Bi, Nb, Si, Zn, Ga, Ge, Sn, Ba, W, Na, and K. 0.98≦x≦1.20, y represents 0.30≦y<1.00, z represents 0<z≦0.50, t represents 0<t≦0.50, p represents 0≦p≦0.05, and y+z+t+p=1.) and a coating portion that coats at least a part of the particle surface of the lithium nickel manganese cobalt composite oxide particle.
9. A method for producing a positive electrode active material for a lithium secondary battery, comprising a step of mixing large particles having an average particle diameter of 7.5 to 30.0 μm obtained by the method for producing the positive electrode active material according to claim 3 or 4 with small particles having an average particle diameter of 0.5 to 7.5 μm obtained by the method for producing the positive electrode active material according to claim 3 or 4.
10. A lithium secondary battery comprising the positive electrode active material for lithium secondary batteries according to claim 1 or 2.
Citation Information
Patent Citations
Lithium nickel manganese cobalt based composite oxide for lithium secondary battery positive electrode material, positive electrode for lithium secondary battery using it, and lithium secondary battery
JP2005025975A
Positive active material for lithium secondary battery, method of manufacturing the same, and lithium secondary battery
JP2011023120A
Positive electrode active material for nonaqueous electrolyte secondary batteries and method for manufacturing the same
JP2016024968A
Positive electrode active material for nonaqueous electrolyte secondary battery, fluid dispersion used in producing the same, and production method thereof
JP2016072071A
Lithium-nickel-cobalt-manganese containing composite oxide, material for positive electrode active material for lithium secondary battery, and methods for producing these
WO2004092073A1